The relationship between critical thinking and student learning independence in mathematics learning in Elementary School - Tilawatila, Wawa; Adinda, Dea; Gunawan, Ridwan (CV. Akademi Merdeka, 2024)
Critical thinking skills are an important foundation for individuals in the modern era. This ability is not only needed at a high level, but also from an early age, including in elementary schools. Unfortunately, its application in elementary schools is still minimal. Assessing the critical thinking skills of 4th grade students in the material of perimeter and area of a square, analyzing its relationship with learning independence, and knowing the level of student understanding of the material. Quantitative research with descriptive and correlational design. A sample of 7 4th grade students was selected by purposive sampling. Data were collected through questionnaires and questions. Data were analyzed using inferential statistics. Students' critical thinking skills are still low. There is a significant positive relationship between learning independence and critical thinking skills. Students' level of understanding of the perimeter and area of a square still needs to be improved. Critical thinking skills of 4th grade students in the material of the perimeter and area of a square need to be improved. Efforts to improve students' critical thinking skills need to be made by paying attention to the important role of learning independence. In addition, learning the perimeter and area of a square needs to be designed more effectively to improve students' understanding. These findings provide important implications for educators to: (1) Increase the focus on developing students' critical thinking skills in learning; (2) Integrate aspects of learning independence in learning to support the development of students' critical thinking skills; (3) Design more effective and student-centered learning of the perimeter and area of a square. This research is expected to contribute to the development of mathematics learning in elementary schools, especially in improving students' critical thinking skills and learning independence in square perimeter and area material.